2013
DOI: 10.1007/s00300-013-1368-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melting Antarctic sea ice on the fate of microbial communities studied in microcosms

Abstract: Although algal growth in the iron-deficient Southern Ocean surface waters is generally low, there is considerable evidence that winter sea ice contains high amounts of iron and organic matter leading to ice-edge blooms during austral spring. We used field observations and shipbased microcosm experiments to study the effect of the seeding by sea ice microorganisms, and the fertilization by organic matter and iron on the planktonic community at the onset of spring/summer in the Weddell Sea. Pack ice was a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
0
24
1
Order By: Relevance
“…Boyd et al (2012) showed that iron flux from melting sea ice is one of the largest iron sources in some regions. Previous studies suggested that iron from melting ice contributed 70-90 % of the total iron supply to surface waters in the East Antarctic, the Weddell Sea, and the Ross Sea during the melting period (Lannuzel et al, 2007(Lannuzel et al, , 2008de Jong et al, 2013). Simulated iron inputs from melting ice in our simulations are generally less than these observational estimates.…”
Section: Iron Sources To Sea Icecontrasting
confidence: 50%
See 2 more Smart Citations
“…Boyd et al (2012) showed that iron flux from melting sea ice is one of the largest iron sources in some regions. Previous studies suggested that iron from melting ice contributed 70-90 % of the total iron supply to surface waters in the East Antarctic, the Weddell Sea, and the Ross Sea during the melting period (Lannuzel et al, 2007(Lannuzel et al, , 2008de Jong et al, 2013). Simulated iron inputs from melting ice in our simulations are generally less than these observational estimates.…”
Section: Iron Sources To Sea Icecontrasting
confidence: 50%
“…Figure 2a shows clear changes of the total iron input to seawater in the Southern Ocean. Previous studies reported that melting ice released 0.30-0.70 µmol Fe m −2 day −1 of iron to surface waters in the East Antarctic, the Weddell Sea, and the Ross Sea (Lannuzel et al, 2007(Lannuzel et al, , 2008; de Jong et al, 2013). Simulated iron fluxes from sea ice to ocean are often less than 1 µmol Fe m −2 month −1 in the Southern Ocean in our simulations, except in the Bellingshausen Sea (> 30 µmol Fe m −2 month −1 ).…”
Section: Impacts Of Sea Ice On the Iron Cycle And Marine Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our DFe concentrations are relatively low compared to other studies collected in winter, spring and summer (Westerlund and Öhman, 1991;de Jong et al, 1998;Lannuzel et al, 2007Lannuzel et al, , 2008Lannuzel et al, , 2013Lannuzel et al, , 2014avan der Merwe et al, 2009van der Merwe et al, , 2011a, our study provides the first evidence that sea ice begins to accumulate DFe as soon as it forms and grows in late autumn and early winter. Following this initial physico-chemical enrichment, DFe concentrations in sea ice subsequently increase as the ice ages through the season, likely due to biogenic processes (Lizotte, 2003;Thomas et al, 2010) or detrital remineralization processes, e.g., transformation of PFe into DFe.…”
Section: Incorporation Of Dissolved Constituents: Conservative and Nomentioning
confidence: 38%
“…Moving from conceptual models to numerical parameterisations requires generalized quantification of processes, something which is lacking for many sea-ice biogeochemical processes. One example is the finding that melting sea ice enriched in iron and organic matter contributes to pelagic ice-edge phytoplankton blooms in the surface ocean (Lancelot et al, 2009;Lannuzel et al, 2013;Wang et al, 2014). While mesocosm experiments confirm the process, field observations remain unclear on the specific mechanism and thus on the large-scale importance of such ice-associated iron fertilization.…”
Section: Figurementioning
confidence: 98%